A Tripartite Game Theoretic Model of the Governance of Music Education as a Discipline in Chinese Higher Education - Xi, Yue; Liu, Yang; Compee, Thitaree (Rajapark International Journal, 2025)
Amid China’s current wave of higher education reform and the elevation of aesthetic education in national cultural strategy, music education as a university discipline remains constrained by structural marginalization, program homogeneity and fragmented governance. This study investigates the institutional dynamics and stakeholder misalignments that impede the high quality development of music education in Chinese universities. a conceptual tripartite game theoretic framework is constructed to model the strategic interactions among government, universities and society, using a static complete information game as the baseline and an evolutionary game extension to examine the stability of different strategy profiles. The analysis shows that under existing incentive structures the government tends to adopt regulation oriented policies, universities converge on conformist disciplinary strategies and societal actors remain weakly engaged, forming a suboptimal yet stable Nash equilibrium characterized by limited innovation and low coordination. Evolutionary dynamics further indicate that, in the absence of effective incentives, feedback channels and trust building, cooperative and innovation oriented strategies cannot become evolutionarily stable. Building on these results, the study proposes an optimized governance model that couples differentiated incentives, tripartite dialogue platforms and institutionalized societal participation to shift the system toward a cooperative equilibrium. The research extends the application of game theory to the governance of arts related disciplines and offers a conceptual foundation for future empirical studies on reform in marginalized academic fields.